The Color Concept of Baju Bodo as Traditional Clothing at Schools in Makassar: Philosophical Perspective and Ethno-Policy Framework - Adela, Dhea; Arnyana, Ida Bagus Putu; Dantes, Nyoman; Ng, Khar Thoe (Universitas Muhammadiyah Purwokerto, 2023)
This study aims to examine the philosophical perspective of the Bodo shirt as one of the traditional clothes of South Sulawesi, which will be applied in the regulations for the use of traditional clothes in schools in Makassar City. This is based on the Minister of Education and Culture Regulation Number 50 of 2022 concerning School Uniforms for Students at the Elementary and Secondary Education Levels. This study used a qualitative approach with an ethnomethodological research design. Data analysis used indexicality analysis and reflexivity analysis. This analysis is intended to provide an overview of group agreement regarding the use of Baju Bodo in elementary school policies as one of the local cultural assets as well as the implementation of ethno-policies for cultural literacy. Determination of informants was carried out by means of purposive sampling, namely researchers who determine the informants themselves to be interviewed based on representative considerations. The informants in this study included teachers, school principals, and community leaders who knew about the philosophy of the Baju Bodo and the color schemes used in the use of Baju Bodo for the Bugis people of South Sulawesi. The results of the study show that in a philosophical study the structure of the baju bodo represents the characteristics of Bugis-Makassar women in general. The distribution of colors in Baju Bodo is divided into two types, the first is in everyday life, such as children under the age of 10 wearing Baju Bodo which are usually called Waju Pella-Pella, this shirt is Ivory Yellow. This shirt is called waju pella-pella or butterfly because it depicts the world of small children who are full of joy. The yellow color of ivory is an analogy for the child to mature quickly and be ready to face life's challenges. Derived from the word maridi (ivory yellow) which means ripe.